PERAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI DALAM PENGARUH HUMAN RESOURCES PRACTICES TERHADAP KOMITMEN KARYAWAN DI POLDA BENGKULU - Oktine Rafida (Jurnal Manajemen dan Pemasaran Jasa, 2016)
The objectives of this research was to find out the effect of human resources practices (reward, training, and person-job fit) on job satisfaction and employee commitment, and the effect of job satisfaction on employee commitment. The methodology of this research was using questionnaire survey approach to collect data for testing the research  hypothesis and regression technique for data analysis. Census was used to analyze the hypothesis. The population were 200 respondents and divided to 187 PNS and 13 PHL of Polda Bengkulu. Finding and contribution in this research was HR practices have a significant effect to employee commitment, human resources practices have a significant effect to job satisfaction, and job satisfaction to employee commitment also have a significant effect. Research limitation or implication in this research was the result can not be applied to other region Polda, or other public organization. This research suggest further investigation is needed to equivalent the result and more extent area of research.